PATIENT NURSING CARE WITH AN EMPATHY APPROACH: INTEGRATING SOCIAL BASED THEORIES AND ISLAMIC RELIGIOUS - Basirun, Muhammad (Prosiding University Research Colloquium, 2024)
A person is called empathic because he is able to feel what others feel. Islam teaches us that other Muslims are brothers and sisters, and as in one body, when one part of the body hurts, the other parts of the body feel the pain. This article details empathy in patient care from an Islamic perspective. Empathy in the care of Muslim patients has existed since 1500 years ago with the view that "Islam teaches us that fellow Muslims are brothers and are like one body and should not harm non-Muslims. Islamic literature in the Qur'an and Hadith is consistent with the results of research by experts on empathy. Research by experts is that empathy is useful in healing, facilitating patient care, facilitating communication, providing satisfaction, facilitating action, facilitating cooperation, providing warmth and increasing affection.